Aurat Perempuan Dalam Al-Qur’an Surat Al-Ahzab Ayat 59: Diskursus Relevansi Cadar Dalam Konteks Indonesia - Eko Zulfikar; Aftonur Rosyad; Nur Afiyah (Jurnal Studi Al-Qur'an, 2022)
This paper explores women's genitalia as far as QS sees it. al-Ahzab [33] verse 59. The specific explanation is related to the use of the veil, which is widespread in the Indonesian context. This study uses a thematic analysis method of the verses of the Qur'an, and it is concluded that there are differences of opinion regarding women's genitalia, especially regarding the face and palms, whether they are classified as aurat or not. This difference then developed in the legal issue of wearing the veil for women. Regarding the use of the veil, scholars consider social conditions so that there are scholars who require women to wear the veil since there has been a lot of slander spread in the community. Some scholars do not require women to wear the veil because the veil is considered a culture that grows from the local culture. However, wearing the veil for women remains relevant in Indonesia because, in addition to the veil protecting women from naughty views of the opposite sex, it will also affect their subconscious to improve religious practices in their lives.